Analysis of the Impact of Demographic Characteristics and Business Conditions on Employee Job Satisfaction - Hüseyin Başlıgil; Umut Hulusi İnan; Fatma Betül Bağlan (Journal of Advanced Research in Natural and Applied Sciences)
Job satisfaction is an important concept in terms of productivity and continuity of enterprises. The decrease in the job satisfaction level of the employees may cause many problems such as slowing down the work and low productivity. In this study, the surveys conducted on 150 employees from 52 sectors were evaluated with the SMART-PLS 3 package program, and the effect of perceptions on business conditions (economic, ergonomic, internal communication, workload level, and career opportunities) on job satisfaction was examined. The topic addressed in the study, the classification of organizational conditions and the methodology employed, contributes to the literature. As a result of the analyses, it was determined that the perceptions of internal communication and career opportunities affect the level of job satisfaction of the employees. In the continuation of the study, the effect of the demographic characteristics of the employees on these perceptions was examined by using the SPSS 22 statistical program. This examination revealed that the gender affected the perception of internal communication and the education level the perception of career opportunities.